Post-operative determinants of chronic pain after primary knee replacement surgery: Analysis of data on 258, 386 patients from the National Joint Registry for England, Wales, Northern Ireland and the Isle of Man (NJR). Issue 1 (March 2021) - Khalid, Sara; Mohammad, Hasan Raza; Gooberman-Hill, Rachael; Garriga, Cesar; Pinedo-Villanueva, Rafael; Arden, Nigel; Price, Andrew; Wylde, Vikki; Peters, Tim J.; Blom, Ashley; Judge, Andrew
Abstract: Objective: To identify post-operative risk factors for the development of chronic pain after knee replacement. Design: Primary knee replacements in persons aged ≥18 years between April 2008 and December 2016 from the National Joint Registry, linked with English Hospital Episode Statistics data, and Patient Reported Outcome Measures. The outcome was chronic pain 6-months after surgery (Oxford Knee pain score). Logistic regression modelling identified risk factors for chronic pain outcome. Results: 258, 386 patients; 56.7% women; average age 70.1 years (SD ​± ​8.8 years). 43, 702 (16.9%) were identified as having chronic pain 6-months post-surgery. Within 3 months of surgery complications were uncommon: intra-operative complications 1224 (0.5%); ≥1 medical complication 6073 (2.4%)); 32, 930 (12.7%) hospital readmissions; 3848 (1.5%) re-operation; 835 (0.3%) revision. Post-surgical risk factors of chronic pain were: mechanical complication of prosthesis odds ratio (OR) 1.56 (95% Confidence Interval 1.35, 1.80); surgical site infection OR 1.13 (0.99, 1.29); readmission OR 1.47 (1.42, 1.52); re-operation OR 1.39 (1.27, 1.51); revision OR 1.92 (1.64, 2.25); length of stay e.g. 6+ vs. <2 days OR 1.48 (1.35, 1.63), blood transfusion OR 0.47 (0.26, 0.86) and myocardial infarction OR 0.69 (0.49, 0.97). Discriminatory ability of the model was only fair (c-statistic 0.71) indicating that post-surgical predictors explain a limited amount of variability in chronic pain. Conclusions: We identified a number of post-operative factors relating to the operation and early recovery that are associated with chronic pain following primary knee replacement. The model had weak discriminatory ability indicating that there remains considerable unexplained variability in chronic pain outcome.